2012
DOI: 10.4236/ajps.2012.31001
|View full text |Cite
|
Sign up to set email alerts
|

New Pineapple Somaclonal Variants: P3R5 and Dwarf

Abstract: The Food and Agriculture Organization has highlighted pineapple as one of the most important tropical fruits. Since classical pineapple breeding is difficult, biotechnology has emerged as an attractive instrument. We obtained two new pineapple somaclonal variants derived from in vitro culture of cv. Red Spanish Pinar: P3R5 and Dwarf. The AFLP analysis revealed an existing genetic distance. So far 44 phenotype indicators selected due to their relation to a wide range of important agricultural, morphological and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(12 citation statements)
references
References 48 publications
0
12
0
Order By: Relevance
“…)Spineless variantJaya et al (2002)Cvs. P3R5 and Dwarf, variation in fruit color, growth habit, fruit size and length of plant generation cyclePérez et al (2009, 2012)43Potato ( Solanum tuberosum L.)Non-browning var. White BaronArihara et al (1995)Somaclones for heat toleranceDas et al (2000)Somaclones IBP-10, IBP-27 and IBP-30, derived from cultivar Desiree, showed higher resistance to Alternaria solani and Streptomyces scabiei Veitia-Rodriguez et al (2002)Improved size, shape, appearance, starch content and starch yieldThieme and Griess (2005)Superior processing attributes than cv.…”
Section: Application Of Somaclonal Variationsmentioning
confidence: 99%
“…)Spineless variantJaya et al (2002)Cvs. P3R5 and Dwarf, variation in fruit color, growth habit, fruit size and length of plant generation cyclePérez et al (2009, 2012)43Potato ( Solanum tuberosum L.)Non-browning var. White BaronArihara et al (1995)Somaclones for heat toleranceDas et al (2000)Somaclones IBP-10, IBP-27 and IBP-30, derived from cultivar Desiree, showed higher resistance to Alternaria solani and Streptomyces scabiei Veitia-Rodriguez et al (2002)Improved size, shape, appearance, starch content and starch yieldThieme and Griess (2005)Superior processing attributes than cv.…”
Section: Application Of Somaclonal Variationsmentioning
confidence: 99%
“…AFLP analysis is commonly used to assess the genetic conformity of plants regenerated by in vitro culture (Aversano et al 2011;Mehta et al 2011) or to detect somaclonal variations (Mo et al 2009;Perez et al 2012). An analysis was performed on the rhizome-propagated plants, short-term culture (ST) in vitro-propagated plants (''vitroplants'') and long-term culture (LT) in vitro-propagated plants.…”
Section: Aflp Analysismentioning
confidence: 99%
“…Table 1 shows the effects of the second experiment. Electrolyte leakage and chlorophyll b concentration were the most modified indicators by the different times of seed exposure performed a comprehensive literature search, we have not found any procedure similar and simpler to the one described in this paper, except for our previous publications (Cejas et al, 2012;Gomez-Pando et al, 2009;González et al, 2010;González et al, 2013;Pérez et al, 2013;Pérez et al, 2012;Zevallos et al, 2013a;Zevallos et al, 2013b), not focused on the use of statistical or mathematical methods, just on the results.…”
Section: Resultsmentioning
confidence: 76%